Flux-dependent Epitaxial Recrystallization of Amorphized Si(111) Layers Due to Oblique Argon Ion Sputtering. Issue 205 (12th February 2020) - Gupta, Divya; Kumari, Rimpi; Chawla, Mahak; Umapathy, G.R.; Aggarwal, Sanjeev
Abstract: Si(111) substrates, having more atoms available at the surface, are currently being exploited for nano-device fabrication. Epitaxial recrystallization of Si(111) layers amorphized under 80 keV Ar + ion sputtering at off-normal incidence of 50° with 1 × 10 17 to 5 × 10 17 Ar + cm −2 has been investigated. Good epitaxial recrystallization under thermal annealing treatment at 1123 K has been observed. RBS/C demonstrates nonlinear behavior of amorphized and recrystallized layer thickness with irradiation fluence. Considerable stress still remains in the recrystallized layers as revealed by Raman studies. The correlation of the induced stress with amorphization and recrystallization has been established and finally the recrystallization mechanism has been discussed.